Real-world sinonasal outcomes in patients with primary diffuse chronic rhinosinusitis treated with mepolizumab across polyp phenotypes - Kumar, Nitish; Patel, Evani; Marino, Michael J.; Lal, Devyani (Frontiers in Immunology, 2026)
BackgroundMepolizumab blocks IL-5, targeting eosinophilic type-2 inflammation. Due to existing phenotype driven patient selection, evidence of its effectiveness in primary diffuse CRS and CRS without nasal polyps (CRSsNP) and in real-world populations is limited. Our objective was to evaluate the real-world effectiveness of mepolizumab in patients with primary diffuse CRS, regardless of nasal polyp status, and to assess outcomes across CRS phenotypes and prior surgical history.MethodsAdults with primary diffuse CRS treated with mepolizumab for ≥6 months were identified. Pre- and post-therapy outcomes included serum eosinophil counts, Lund-Mackay CT scores, Lund-Kennedy endoscopic scores, and SNOT-22 symptom scores. Subgroup analyses were performed by CRS phenotype (CRSwNP vs. CRSsNP) and prior endoscopic sinus surgery (ESS). Biologic switching and discontinuation were recorded.ResultsAmong 277 patients (mean age 60.8 ± 14.7 years; 54.9% female), 93.5% had type-2 comorbidities, 29.6% had CRSsNP, and 27.8% were ESS-naïve. The median duration of mepolizumab therapy was 31 months. Mepolizumab therapy significantly reduced serum eosinophils (median 0.57 to 0.07 ×109/L, p<0.001) and Lund-Mackay scores (median 14 to 10, p<0.001), which was consistent across all subgroups. Improvements in SNOT-22 and endoscopic scores were modest and not consistently significant. CRSwNP patients were more likely to undergo ESS during therapy, but time to first post-therapy ESS was longer than in CRSsNP. There were no differences in likelihood of undergoing ESS during therapy, time to subsequent ESS, or oral corticosteroid use between prior ESS and ESS-naïve patients. Biologic switching occurred in 24.9%, and discontinuation in 16.6%, primarily due to disease recalcitrance.ConclusionMepolizumab effectively reduced systemic eosinophilia and radiographic disease burden in primary diffuse CRS, independent of phenotype or prior ESS. Symptom improvement was variable, highlighting the heterogeneity of clinical response. These findings support an endotype-driven approach to biologic therapy and suggest that IL-5 blockade may benefit selected CRSsNP patients.